ANALISIS EFEKTIVITAS PENERIMAAN BEA BALIK NAMA KENDARAAN BERMOTOR PADA UPPD SAMSAT BANJARMASIN II (Studi Kasus Tahun 2018 – 2020) - Cholifah Awaliyah; Saprudin (Universitas Lambung Mangkurat, 2021)
This study aims to determine the effectiveness of the receipt of transfer fees for motorized vehicles and to find out what factors affect the effectiveness of receiving transfer fees for motorized vehicles at UPPD Samsat Banjarmasin II 2018-2020. The type of data used is quantitative data such as target data and realization of transfer fees for motorized vehicles from 2018-20220 and qualitative data such as interviews with UPPD Samsat Banjarmasin II employees. The results showed that the transfer fee for motorized vehicles at UPPD Samsat Banjarmasin II was considered effective.